2005
DOI: 10.1063/1.2102071
|View full text |Cite
|
Sign up to set email alerts
|

Formation rates of iron-acceptor pairs in crystalline silicon

Abstract: The characteristic association time constant describing the formation of iron-acceptor pairs in crystalline silicon has been measured for samples of various p-type dopant concentrations and species ͑B, Ga, and In͒ near room temperature. The results show that the dopant species has no impact on the pairing kinetics, suggesting that the pairing process is entirely limited by iron diffusion. This conclusion was corroborated by measurement of the activation energy of pair formation, which coincides with the migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 23 publications
(39 reference statements)
2
46
0
Order By: Relevance
“…The same methodology applied by Macdonald et al [6] to extract  assoc from the effective lifetime exponential decay curves has been used in this paper. figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same methodology applied by Macdonald et al [6] to extract  assoc from the effective lifetime exponential decay curves has been used in this paper. figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…[2,3,4] However, recent measurements of Fe i -B association time constants ( assoc ) utilizing a temperature controlled WCT-100 Sinton Consulting instrument [5], have indicated that the pre-factor in the equation published by Macdonald el al. [6] (5x10 5 cm -3 K -1 ) requires some adjustment. In addition, the original measurements were accurate to ±3K.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the association of FeB pairs needs an activation energy of 0.60 eV [2]. This process is limited by the Fe diffusion towards substitutional B in silicon [2,9,10], with a diffusion constant (D 0 ) being in the range of 0.6 À1.8 Â 10 À 3 cm 2 /s [2,11]. For the dissociation of FeB pairs, the activation energy is 1.17 À 1.2 eV, and the corresponding attempt frequency is 1.8 À5 Â 10 10 s À 1 [2].…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of using gallium-doped wafers is that they are free of any B-O related LID effects. However, like boron-doped wafers, they are susceptible to the formation of acceptor-iron pairs [53,54]. A weakness of gallium-doped ingots is the substantially lower segregation coefficient for gallium (8 × 10 −3 ) than that for boron (0.8) [55,56].…”
Section: Decreasing the Boron Doping Concentrationmentioning
confidence: 99%